The Risk of Incident Venous Thromboembolism Attributed to Overweight and Obesity: The Tromsø Study - Frischmuth, Tobias; Tøndel, Birgitte G.; Brækkan, Sigrid K.; Hansen, John-Bjarne; Morelli, Vânia M. (Thrombosis and Haemostasis, 2023)
Background Obesity is a well-established risk factor for venous thromboembolism (VTE). However, data on the proportion of incident VTEs attributed to overweight and obesity in the general population are limited.Objective To investigate the population attributable fraction (PAF) of VTE due to overweight and obesity in a population-based cohort with repeated measurements of body mass index (BMI).Methods Participants from the fourth to seventh surveys of the Tromsø Study (enrolment: 1994–2016) were followed through 2020, and all incident VTEs were recorded. In total, 36,341 unique participants were included, and BMI measurements were updated for those attending more than one survey. BMI was categorized as <25 kg/m2, 25–30 kg/m2 (overweight), and ≥30 kg/m2 (obesity). Time-varying Cox regression models were used to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). The PAF was estimated based on age- and sex-adjusted HRs and the prevalence of BMI categories in VTE cases.Results At baseline, the prevalence of overweight and obesity was 37.9 and 13.8%, respectively. During a median follow-up of 13.9 years, 1,051 VTEs occurred. The age- and sex-adjusted HRs of VTE were 1.40 (95% CI: 1.21–1.61) for overweight and 1.86 (95% CI: 1.58–2.20) for obesity compared with subjects with BMI <25 kg/m2. The PAF of VTE due to overweight and obesity was 24.6% (95% CI: 16.6–32.9), with 12.9% (95% CI: 6.6–19.0) being attributed to overweight and 11.7% (95% CI: 8.5–14.9) to obesity. Similar PAFs were obtained in analyses stratified by sex and VTE subtypes (provoked/unprovoked events, deep vein thrombosis, pulmonary embolism).Conclusion Our findings indicate that almost 25% of all VTE events can be attributed to overweight and obesity in a general population from Norway.
Keywords: obesity; overweight; population attributable fraction; venous thromboembolism